My grandpa is amazing - Butterworth, Nick. (Cambridge, Mass. : Candlewick Press, 2003)
A child describes an amazing grandfather.
"First published in Great Britain in 1991 by Walker Books Ltd., London"--P. facing t.p.
1.5.
1.5
K-3
Keywords: Grandfathers -- Fiction; Grandparent and child -- Fiction; Grandfathers -- Fiction; Grandparent-grandchild relationship -- Fiction